2018
DOI: 10.1186/s13018-018-0823-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo cartilage tissue engineering

Abstract: BackgroundBiologic treatment options for cartilage injuries require chondrocyte expansion using cell culture. Clinical application is accomplished in two surgical sessions and is expensive. If isolation of chondrocytes and stimulus for proliferation and extracellular matrix synthesis can be achieved in vivo, the treatment can be performed in one session and the cost can be reduced.MethodsA 2.5-cm diameter full-thickness chondral defect was created in the knees of five groups of sheep. In one group, some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Within 3 months, the ICRS scores in Groups 2 and 3 compared to the Group 1 showed significant improvements in all scores except for the cell distribution score. Within 6 months, the evaluation of the ICRS scores showed that the Groups 2 and 3 had significantly higher scores than the Group 1 on all scores (Figure 8; Chen et al, 2018; Gurer, Cabuk, Karakus, Yilmaz & Yilmaz, 2018). H&E staining showed that Groups 3 and 2 had more chondrocyte like cells in the renewed space with cartilage cavity (Figure 9a–f).…”
Section: Resultsmentioning
confidence: 95%
“…Within 3 months, the ICRS scores in Groups 2 and 3 compared to the Group 1 showed significant improvements in all scores except for the cell distribution score. Within 6 months, the evaluation of the ICRS scores showed that the Groups 2 and 3 had significantly higher scores than the Group 1 on all scores (Figure 8; Chen et al, 2018; Gurer, Cabuk, Karakus, Yilmaz & Yilmaz, 2018). H&E staining showed that Groups 3 and 2 had more chondrocyte like cells in the renewed space with cartilage cavity (Figure 9a–f).…”
Section: Resultsmentioning
confidence: 95%
“…A few in vivo animal studies assessed the effects of collagenase treatment on cartilage repair. Gurer et al tried to enhance cartilage regeneration in the knees of sheep by using collagen membrane soaked with collagenase [ 25 ]. Sueyoshi et al revealed that collagenase treatment was effective on cubic micro-cartilage to expand cartilage regeneration capacity in ear cartilage tissue engineering [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most TE technology for treating articular cartilage defects requires opening the joint cavity to place a biological scaffold, which inevitably causes great damage to the surrounding tissues of the joint [ 77 ]. However, due to its unique size advantage, microcarriers can be localized to cartilage defect sites that contain biologically active microtissues or seed cells by injection, which can reduce trauma caused by large-scale incisions [ [78] , [79] , [80] ].…”
Section: Overview Of the Advantages Of Microcarriers In The Treatmentmentioning
confidence: 99%